Socratic questioning-fostering high school learners speaking skills in an ecuadorian public school - Parra Manchay, Luz Maria (2021)
Speaking is one of the four macro skills required to communicate effectively in English (Boonkit, 2010). This action research investigated the use of SQ to foster the speaking skills of high school learners in an Ecuadorian public school. Sixteen participants, aged 16-18, were selected as a convenience sample and asked to participate in a four- week study. Before the intervention, participants responded to a questionnaire to get a baseline regarding speaking skills. The means of observation, journals, and interviews were used to collect data. Moreover, the researcher used triangulation to add validity and reliability to the study. The findings indicated that the SQ had a positive effect on participants’ speaking skills.